The Exsistence Of Mindring And Its Risks In An Islamic Perspective - Febi Suprobo; Maretha Ika Prajawati (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2023)
One of the informal economic institutions in Harjokuncaran Village is mindring. Mindring credit still exists in Harjokuncaran Village because it does not charge a guarantee of valuables as a condition. This study aims to determine the process of implementing mindring practices and the risks that arise from mindring practices in Harjokuncaran Village, Sumbermanjing Wetan, Malang Regency. The author uses qualitative research methods in this study. The purpose of this method is to provide a more in-depth explanation of the results of observations, interviews, and documentation obtained by the author regarding the description of the implementation of mindring and the risks that arise from this business in Harjokuncaran Village, Malang Regency. In this study, the main informants are mindring business actors. Data collection techniques used are observation, interviews, and documentation. Data analysis methods used include data reduction, data display, and conclusion. The mindring process is easy and flexible, starting from ordering, delivery and payment. The risks that arise include consumers who do not pay regularly, installment periods that make consumers delay payments, and finally consumers who disappear before completing their credit. The limitations of researchers in conducting this research are changes in market conditions that make it difficult for researchers to find respondents, because with conditions like this all online, many mindring respondents have switched professions.